2023
DOI: 10.3389/fonc.2023.1166245
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning models combining computed tomography semantic features and selected clinical variables for accurate prediction of the pathological grade of bladder cancer

Abstract: ObjectiveThe purpose of this research was to develop a radiomics model that combines several clinical features for preoperative prediction of the pathological grade of bladder cancer (BCa) using non-enhanced computed tomography (NE-CT) scanning images.Materials and methodsThe computed tomography (CT), clinical, and pathological data of 105 BCa patients attending our hospital between January 2017 and August 2022 were retrospectively evaluated. The study cohort comprised 44 low-grade BCa and 61 high-grade BCa pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In patients with breast cancer, a substantial association has been shown between GLCM idmn and one‐year relapse‐free survival 42 . Moreover, it was discovered that GLRLM may be used to predict acute pulmonary thromboembolism, 43 whereas NGTDM is linked to the prediction of pathological grade in bladder cancer 44 . The aforementioned studies have demonstrated that radiomics features not only enable the expression of tumor heterogeneity, which is challenging to detect visually, through digital information but also exhibit potential for evaluating tumor prognosis 12 .…”
Section: Discussionmentioning
confidence: 99%
“…In patients with breast cancer, a substantial association has been shown between GLCM idmn and one‐year relapse‐free survival 42 . Moreover, it was discovered that GLRLM may be used to predict acute pulmonary thromboembolism, 43 whereas NGTDM is linked to the prediction of pathological grade in bladder cancer 44 . The aforementioned studies have demonstrated that radiomics features not only enable the expression of tumor heterogeneity, which is challenging to detect visually, through digital information but also exhibit potential for evaluating tumor prognosis 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Our study confirmed this association, as the radiomics scores derived from planning CT images were significantly higher in the pCR group, with all corresponding AUC values being greater than or nearly 80%. While some studies favored SVM classifiers over the LASSO or RF methods [32][33][34][35] in the development of radiomics models, other studies reported the superior performance of the LASSO or RF classifiers [27,[36][37][38][39]. These divergent findings suggest that the choice of machine learning model influenced the predictive performance.…”
Section: Discussionmentioning
confidence: 99%
“…There has been promising recent work applying deep learning and multiomics methods to UTUC. Future work may incorporate the direct use of radiologic imaging in these machine learning models for UTUC detection, subtyping, and prognostication, as has been performed in abundance for urothelial cancer of the bladder [32,33].…”
Section: Ai and Multiomics In The Classification And Prognostication ...mentioning
confidence: 99%